2018
DOI: 10.1111/ans.14361
|View full text |Cite
|
Sign up to set email alerts
|

Robotic‐assisted radical cystectomy with intracorporeal urinary diversion versus open: early Australian experience

Abstract: Early results demonstrate that the safe introduction of RARC with ICUD in Australia is potentially feasible without compromising perioperative and oncological outcomes. Future randomized trial with larger numbers will be required for further analysis in the Australian setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
13
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 39 publications
3
13
1
Order By: Relevance
“…In our experience of robotic radical cystectomy and intracorporeal diversion at The Royal Melbourne Hospital in a smaller series, our outcomes were similar to the Brisbane report . Long operative times in the learning curve and anastomotic uretero‐ileo‐stricture remain problematic in the early phase.…”
supporting
confidence: 78%
“…In our experience of robotic radical cystectomy and intracorporeal diversion at The Royal Melbourne Hospital in a smaller series, our outcomes were similar to the Brisbane report . Long operative times in the learning curve and anastomotic uretero‐ileo‐stricture remain problematic in the early phase.…”
supporting
confidence: 78%
“…Post‐operative complications are listed in Table . Post‐operative complications were characterized at 90 days using the Clavien–Dindo classification . Most patients experienced uncomplicated recoveries (44%) or low‐grade post‐operative complications (Clavien–Dindo I–II 32%).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, several studies have compared RARC to open RC (ORC) and reported improved or comparable surgical outcomes including blood loss, length of hospital stay (LOS) and post‐operative complications . To date, a single Australian series of 26 patients has been reported in the literature …”
Section: Introductionmentioning
confidence: 99%
“…Chow et al . have demonstrated that lymph node yields and surgical margin status are equivalent between the two cystectomy methods . There are unfortunately no long‐term oncological outcomes reported from RARC; however, based on early short‐term reports, it is unlikely that they will be inferior to ORC.…”
mentioning
confidence: 85%
“…In this month’s issue, Chow et al . have demonstrated how robotic assisted RC (RARC) can be safely introduced in a number of hospitals in Melbourne …”
mentioning
confidence: 99%